SURVEY OF FRESHWATER TURTLES IN SALMON BROOK, NASHUA, NEW HAMPSHIRE, USA. - Clement, Danielle; Fontaine, Jeremy; Demers, Shanna (InSight: Rivier Academic Journal)
New Hampshire is home to eight native species of freshwater turtles, including one introduced species, Trachemys scripta elegans (Red Eared Slider). Literature on freshwater turtle populations and ranges throughout New England is not as complete as in other parts of the United States. Here, we provide population parameters for three native species of freshwater turtles: Sternotherus odoratus (Common Musk Turtle), Chelydra serpentina (Snapping Turtle), and Chrysemys picta (Eastern Painted Turtle) that we captured using baited hoop nets or by hand over three years from 2021 to 2023. We obtained biometric data, including carapace and plastron length and width, mass, and visual sex on 404 C. picta, 19 S. odoratus, 21 C. serpentina, two T. scripta elegans, and one state-endangered E. blandingii. Turtles that were recaptured during the survey were remeasured unless caught earlier in the same trapping season/session. A minimum of ten traps were set at three locations throughout a small river tributary, Salmon Brook, in southern Nashua, New Hampshire, USA, during May and July 2021, April 2022, May and September 2023. This survey established prevalent species found in the Salmon Brook tributary. Data collected during the three-year period will be used as baseline information for a longer-term population study assessing spatial and temporal variation in the observed species.